2021
DOI: 10.1152/japplphysiol.00647.2020
|View full text |Cite
|
Sign up to set email alerts
|

Physiological demands of running at 2-hour marathon race pace

Abstract: The requirements of running a 2 hour marathon have been extensively debated but the actual physiological demands of running at ~21.1 km/h have never been reported. We therefore conducted laboratory-based physiological evaluations and measured running economy (O2 cost) while running outdoors at ~21.1 km/h, in world-class distance runners as part of Nike's 'Breaking 2' marathon project. On separate days, 16 male distance runners (age, 29 ± 4 years; height, 1.72 ± 0.04 m; mass, 58.9 ± 3.3 kg) completed an increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 62 publications
4
98
0
Order By: Relevance
“…Although reasonably likely to affect the anaerobic capacity of the competitors, we cannot speculate on how this might influence the CR. This study showed that small variations in pace, representing a CV of running speed from 0 to 7%, which is within the range observed in competitive races [ 3 , 4 , 5 , 8 ], do not significantly affect CR, HR or blood lactate, at least at velocities below the VT.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although reasonably likely to affect the anaerobic capacity of the competitors, we cannot speculate on how this might influence the CR. This study showed that small variations in pace, representing a CV of running speed from 0 to 7%, which is within the range observed in competitive races [ 3 , 4 , 5 , 8 ], do not significantly affect CR, HR or blood lactate, at least at velocities below the VT.…”
Section: Discussionsupporting
confidence: 79%
“…Given that VO 2 max has largely been unchanged in elite runners over the last half-century, and evidence is lacking on systematic changes in anaerobic capacity, only VT, fractional utilization and CR provide reasonable candidates for the continuing improvement in running records. Fractional utilization is of established importance within competitive runners [ 6 ] and is particularly high in the most elite runners [ 7 , 8 ]. The CR is thought to vary meaningfully amongst runners and is particularly low in elite runners [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sub-2-hour marathon performance by Eliud Kipchoge ( 1:59:40, hr:min:sec ) in late 2019 fascinated the public, athletes and scientists (7, 10, 12), not unlike the first sub-4-minute mile run by Sir Roger Bannister in 1954. This interest in the physiology of fast marathons is exemplified by the associated Viewpoint in The Journal of Applied Physiology (11) and ∼40 accompanying commentaries (22).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological requirements for fast marathon performances, including 2-hour marathon pace (10), are well-known and include an optimal combination of exceptional , ‘lactate threshold’, and running economy (11). Although and ‘lactate threshold’ have been optimized by impressive training loads of elite athletes for many decades (11), improved running economy is thought to be deterministic in the most elite runners and is now the target of technological innovation to enhance human performance beyond current limits.…”
Section: Introductionmentioning
confidence: 99%